SISTEM INFORMASI HONOR MENGAJAR DOSEN STMIK INDONESIA PADANG - Rajab -; M. Amrin Erwin (JURNAL AKADEMIKA)
This research was done at sekolah tinggi manajemen informatika dan komputer (STMIK) indonesia padang. this study concerned on the information system of lecturer’s honorarium in stmik indonesia padang. based on the observation, it was found that the data processing system of lecturer’s honorarium payment was done manually without any programing language. thus, the researchers designed an application program of lecturer’s honorarium information system for stmik indonesia padang. the result of this research shows that the designed application program was useful and easy-to-use during processing the data. the data processing included the lecture’s data input, the course/subject, and the lecturer’s honorarium. the output/product of this program is the report of lecturer’s honorarium payment of stmik indonesia padang.